The trail of gold and silver : mining in Colorado, 1859-2009 - Smith, Duane A. (Timberline books., 2009)
Details Colorado's mining saga - a story that stretches from the beginning of the gold and silver mining rush in the mid-nineteenth century into the twenty-first century. Gold and silver mining laid the foundation for Colorado's economy, and 1859 marked the beginning of a fever for these precious metals. Mining changed the state and its people forever.